Diana Farr Louis: Fasting and Feasting in Crete - Jaine, Tom (Petits Propos Culinaires, 2024)
Diana Farr Louis: Fasting and Feasting in Crete: Kedros Publications, Athens, 2001: ISBN 9600 19631: 239 pp., many sepia illus., h/b, 25 euros.